PROFESSIONAL DEVELOPMENT OF ENGLISH LANGUAGE TEACHER: SOME PRACTICAL ASPECTS - Nenko, Yuliia (Mountain School of Ukrainian Carpaty, 2018)
The aim of the study is to present the results of the theoretical analysis of effective ways of professional self-development and self-improvement of English language teachers in accordance with new educational standards. The key methods of research are theoretical methods of analysis, synthesis and generalization of pedagogical and psychological literature. The article addresses the problem of professional development of the English teacher. The interpretation of the concept of «continuous professional development», its characteristics are revealed. The theoretical bases of existing leading modern approaches to the organization of professional self-development of pedagogical workers, including English language teachers, have been analyzed. One of the priority directions of the reform of the national education system is the renewal of the teacher’s corps, constant professional development of teachers, expansion of professional competencies and improvement of their qualification through formal, informal and informal additional education for professional and personal self-development of pedagogical workers. The author’s consideration of the concept of «continuous professional development of the teacher» leads to the conclusion that the process of professional formation and development of teachers should acquire signs of continuity, continuity at its various stages, create the preconditions for satisfying both the educational needs of the teacher's personality and social order for the qualitative training of the competent specialist and contribute to the construction of an individual trajectory of professional and personal self-improvement of the teacher.